Measures of cognitive reserve in Alzheimer's disease=Medidas de reserva cognitiva na doença de Alzheimer - Sobral, M.; Pestana, M.H.; Paúl, C. (Trends in Psychiatry and Psychotherapy, 2014)
Introduction: Cognitive reserve (CR), a hypothetical construct used to obtain information about cognitive aging, describes the capacity of the adult brain to cope with the effects of neurodegenerative processes. This study evaluated CR using a CR questionnaire (CRQ) and a set of variables (education, leisure activities, lifelong occupation) that inform CR. It also developed a CR index, validated the CRQ, and examined the correlation between the different CR measures. Methods: Functional and neuropsychological capacities of 75 outpatients (mean age: 80.2 years) with a probable AD diagnosis were evaluated. Socio-demographic data and clinical variables were collected. Patients completed two questionnaires: the Participation in Leisure Activities throughout Life questionnaire, and the CRQ. Results: Participants with a greater CR had higher scores in cognitive tests than the elderly with a lower CR. A CR index was developed. CRQ reliability was 0.795 (Cronbach’s alpha). There was a close association between the CR Index and the CRQ. Conclusions: This study found an association between CR measures and education, occupation and participation in leisure activities. The CRQ seems to be a suitable instrument to measure CR in Portuguese populations. INTRODUÇÃO: A reserva cognitiva (RC), um construto usado para informar sobre o envelhecimento cognitivo, descreve a capacidade do cérebro adulto em lidar com os efeitos de processos neurodegenerativos. Este estudo teve como objetivos avaliar a RC com o Questionário de RC (QRC) e através de variáveis (escolaridade, actividades de lazer, ocupação ao longo da vida) que informam sobre a RC; desenvolver um índice de RC; validar o QRC; e correlacionar as diferentes medidas de RC. MÉTODOS: Foram avaliadas as capacidades funcionais e neuropsicológicas de 75 doentes (idade média: 80,2 anos) com diagnóstico de provável doença de Alzheimer, seguidos em ambulatório. Os dados recolhidos incluíram variáveis sócio-demográficas e clínicas. Os pacientes completaram dois questionários: Participação em Atividades de Lazer ao Longo da Vida; e QCR. RESULTADOS: Os doentes com os níveis mais elevados de RC obtiveram os valores mais elevados nos testes cognitivos. Neste estudo foi desenvolvido um IRC. O QRC (versão portuguesa) teve uma fidelidade de 0,795 (alpha de Cronbach) e foi demonstrada uma associação alta entre o IRC e o QRC. CONCLUSÕES: Verificou-se a existência de uma associação entre as medidas de RC e a escolaridade, ocupação e participação em atividades de lazer. O CRQ pode ser considerado um instrumento adequado para medir o CR da população portuguesa.